Oxidative Insults of 2, 2-dichlorovinyl-dimethyl phosphate (DDVP), an Organophosphate Insecticide in Rats Brain (Fountain Journal of Natural and Applied Sciences, 2012)
The oxidative insult of 2, 2-dichlorovinyl-dimethyl phosphate (DDVP) in male rats brain was investigated. Rats were grouped into four: A, B, C and D where A, (the control) received orally 1 mL of distilled water; B, C and D (test groups) received orally 2.5, 5 and 10 mg/kg body weight of DDVP respectively for 28 days. DDVP administration caused significant decrease (P